No to religious intolerance - Abd Razak, Dzulkifli (2005)
RECENTLY, we read about a protest by the Sikh community against a film screened in India. The title Jo Bole So Nihaal is similar to a popular term only spoken in a pious manner in Sikh temples or on the battlefield. The Sikhs regarded this as an insult to their religion and demanded that the Hindi film be withdrawn. Just like the Sikhs, Muslims, too, experience many insults and improprieties, some seemingly out of ignorance, others out of arrogance. Certain groups in the West are in fact eager to flush down the toilet anything to do with Islam. This can be traced way back in history, to the growth of Orientalism as a branch of study designed to demean Islam at the slightest excuse. The seminal work on the subject by the late intellectual giant, Edward Said, said it all. He argues that the Middle East and Asia are viewed with prejudice and racism.